Islamic marketing mediation model in the influence of product innovation on the financial performance of Halal-certified MSMEs in Samarinda, Indonesia - Jubaidi, Jubaidi; Kartini, Enny (Journal of Islamic Economics Lariba, 2026)
IntroductionFinancial performance is a critical indicator of sustainability and competitiveness for halal-certified Micro, Small, and Medium Enterprises, especially in markets where consumers increasingly demand halal compliance, product quality, ethical business conduct, and transparent value communication. Although product innovation is widely recognized as a strategic capability, its financial benefits may depend on the extent to which innovation is communicated through Islamic marketing principles.ObjectivesThis study examines the influence of product innovation on the financial performance of halal-certified Micro, Small, and Medium Enterprises in Samarinda, Indonesia. It also analyzes the mediating role of Islamic marketing in strengthening the relationship between product innovation and financial performance.MethodThis study employed an explanatory quantitative design using Structural Equation Modeling based on Partial Least Squares. Primary data were collected through structured questionnaires from 215 owners and managers of halal-certified Micro, Small, and Medium Enterprises in Samarinda. The research model tested the direct effects of product innovation on financial performance, product innovation on Islamic marketing, Islamic marketing on financial performance, and the indirect effect of product innovation on financial performance through Islamic marketing.ResultsThe findings show that product innovation has a positive and significant effect on the financial performance of halal-certified Micro, Small, and Medium Enterprises. Product innovation also significantly improves Islamic marketing practices. In addition, Islamic marketing has a positive effect on financial performance and partially mediates the relationship between product innovation and financial performance. These results indicate that innovation generates stronger financial outcomes when supported by marketing practices grounded in honesty, transparency, trustworthiness, ethical promotion, fair pricing, and halal-oriented communication.ImplicationsThis study suggests that halal-certified Micro, Small, and Medium Enterprises should not rely solely on halal certification or product renewal. Sustainable financial performance requires the integration of product innovation with Islamic marketing values that build consumer trust, strengthen market differentiation, and enhance business resilience.Originality/NoveltyThis study contributes to the halal business and Islamic marketing literature by developing an Islamic Marketing Mediation Model that explains how product innovation is converted into financial performance among halal-certified Micro, Small, and Medium Enterprises in a regional Indonesian context.